The burden of cardiovascular disease in sub-Saharan Africa - Hewitson, J.; Brown, Michael S.; Hugo-Hamman, C.; Zühlke, L; Hoosen, E.; Harrisberg, J. (SA Heart Journal, 2017)
Correspondence: The burden of cardiovascular disease in sub-Saharan Africa by Anthony Mbewu.